2020
DOI: 10.1186/s12981-020-00303-1
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with efavirenz-containing treatments in newly antiretroviral therapy initiated HIV patients in Ecuador

Abstract: Background: It is well known that people living with HIV (PLWH) is in higher risk for the development of depression and it has also been suggested that the use of efavirenz into the antiretroviral regimens increases even that risk. Objective: To evaluate the effect of efavirenz-containing antiretroviral regimens on the development of depression in newly ART initiated HIV patients in Ecuador. Methods: In a prospective cohort study from June 2016 to May 2017, all newly HIV diagnosed patients at the HIV/AIDS Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
0
17
1
2
Order By: Relevance
“…Excessive production of proin ammatory cytokines during neuroin ammation have been implicated in cognitive de cits and anxiety disorders (Charlton et al, 2018;Li et al, 2019). Interestingly, in the post-era of HAART, people living with HIV have experienced an improvement in motor skills and verbal uency but show impaired executive functions and anxiety-like behaviour (Checa et al, 2020;Heaton et al, 2011). In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high (Nuesch et al, 2009;Rabkin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive production of proin ammatory cytokines during neuroin ammation have been implicated in cognitive de cits and anxiety disorders (Charlton et al, 2018;Li et al, 2019). Interestingly, in the post-era of HAART, people living with HIV have experienced an improvement in motor skills and verbal uency but show impaired executive functions and anxiety-like behaviour (Checa et al, 2020;Heaton et al, 2011). In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high (Nuesch et al, 2009;Rabkin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high (Nuesch et al, 2009;Rabkin et al, 2000). The most used components of HAART (Efavirenz and Tenofovir) have been reported to cross the blood-brain barrier, causing mitochondrial dysfunction and some neurological-related adverse effects like depression and anxiety disorder (Checa et al, 2020;Chen et al, 2019). Several studies have suggested that the prefrontal cortex and its circuitry play a vital role in anxiety-like behaviour in animals and humans (Hare & Duman, 2020;Likhtik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive production of pro-inflammatory cytokines during neuroinflammation has been implicated in cognitive deficits and anxiety disorders ( Charlton et al, 2018 , Li et al, 2019 ). Interestingly, in the post-era of HAART, people living with HIV have experienced an improvement in motor skills and verbal fluency but show impaired executive functions and anxiety-like behaviour ( Heaton et al, 2011 , Checa et al, 2020 ). In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high ( Nuesch et al, 2009 , Rabkin et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the post-era of HAART, people living with HIV have experienced an improvement in motor skills, verbal fluency, but executive functions and anxiety-like behaviour remain dominant impairments (Checa et al, 2020;Heaton et al, 2011). In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high (Nuesch et al, 2009;Rabkin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence of anxiety and depression among the patient receiving HAART remains high (Nuesch et al, 2009;Rabkin et al, 2000). The most used components of HAART (Efavirenz and Tenofovir) have been reported to cross the blood-brain barrier, causing mitochondrial dysfunction and some neurological-related adverse effects like depression and anxiety disorder (Checa et al, 2020;Chen et al, 2019). Several studies have suggested that the prefrontal cortex and its circuitry play a vital role in anxiety-like behaviour in animals and humans (Hare & Duman, 2020;Likhtik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%